Sulforaphane Improves Abnormal Lipid Metabolism via Both ERS‐Dependent XBP1/ACC &SCD1 and ERS‐Independent SREBP/FAS Pathways. Issue 6 (23rd February 2018) - Tian, Sicong; Li, Baolong; Lei, Peng; Yang, Xiuli; Zhang, Xiaohong; Bao, Yongping; Shan, Yujuan
Abstract : Scope: To investigate the effect of sulforaphane (SFN) on the abnormal lipid metabolism and underlying mechanisms. Methods and results: Models with abnormal lipid metabolism are established both in rats and human hepatocytes. Hepatic steatosis is detected by hematoxylin and eosin and oil red O staining. The structure of endoplasmic reticulum is visualized by transmission electron microscopy. The expressions of X‐box binding protein 1 (XBP1), protein kinase‐like ER kinase (PERK), sterol regulatory element binding protein‐1c (SREBP1c), and lipogenic enzymes are determined by real‐time PCR and western blot analysis. SFN lowers the content of triglyceride and cholesterol. SFN alleviates the swelling of ER and decreases the perimeter of ER. SFN significantly decreases the expressions of acetyl CoA carboxylase 1 (ACC1), stearoyl‐CoA desaturase 1 (SCD1), and fatty acid synthase. SFN inhibits SREBP1c by blocking the PERK. Meanwhile, SFN suppresses ACC1 and SCD1 via blocking the formation of splicing‐type XBP1. The key roles of XBP1 and SREBP1c in SFN‐reduced lipid droplets are confirmed by a timed sequence of measurement according to time points. Conclusion: SFN improves abnormal lipid metabolism via both ER‐stress‐dependent and ‐independent pathways. Abstract : Sulforaphane (SFN) inhibits lipid synthesis by blocking the endoplasmic reticulum‐stress (ERS). On the one hand, SFN suppresses IRE1 and its downstream transcript (sXBP1), which inactivates acetyl CoA carboxylase 1(ACC1) and stearoyl‐CoA desaturase 1 (SCD1). On the other hand, SFN inhibits the expression of SREBP1 through downregulating PERK or stimulating insulin signal, which leads to the inhibition of fatty acid synthase (FAS).